T cell exhaustion in pediatric B-ALL: current knowledge and future perspectives - Atre, Tanmaya; Reid, Gregor S. D. (Frontiers in Immunology, 2025)
B-cell acute lymphoblastic leukemia (B-ALL) is the most common pediatric malignancy, accounting for 20-25% of all new cancer diagnoses in North American children each year. The leukemia arises, most commonly after a latency of 3–5 years, from a preleukemic B cell precursor population generated in utero. Despite the generally low immunogenicity of B-ALL cells, emerging evidence implicates T cell exhaustion - a state marked by sustained expression of inhibitory receptors and progressive functional decline - as a contributor to disease progression. Expression of inhibitory receptors is frequently detected on T cells from children with B-ALL at diagnosis and during therapy. As T cell exhaustion presents an actionable target for enhancing protective immune activity, in this review we summarize evidence from both clinical and pre-clinical settings for T cell exhaustion during pediatric B-ALL progression and discuss the opportunities and challenges to incorporating immune checkpoint blockade into pediatric B-ALL therapy regimens.